Implementasi Capaian Pembelajaran Informatika Dalam Pembelajaran Matematika Di Sekolah Dasar - Sahrun Nisa; Mai Sri Lena; Hafsah Anas; Tiara Utari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This article aims to compile information on the implementation of informatics learning outcomes (CP) in mathematics education at elementary schools. The study utilizes a descriptive analytical research approach, employing library research methods to gather data from journals, news, and books obtained from both internet sources and digital libraries. Data collection techniques involve conducting a literature review, while qualitative analysis is employed to describe the data obtained through document analysis. The results demonstrate that there are three key elements of informatics learning outcomes that are absent during phase A of mathematics education in elementary schools.